Correction: Ethical challenges of using remote monitoring technologies for clinical research: A case study of the role of local research ethics committees in the RADAR-AD study. - Marijn Muurling; Anna M G Pasmooij; Ivan Koychev; Dora Roik; Lutz Froelich; Emilia Schwertner; Dorota Religa; Carla Abdelnour; Mercè Boada; Monica Almici; Samantha Galluzzi; Sandra Cardoso; et al. (PLoS ONE, 2023)
[This corrects the article DOI: 10.1371/journal.pone.0285807.].